ANALYSIS OF HRM POLICIES AND PRACTICES IN COMMERCIAL BANKS – A STUDY (International Journal of Food and Nutritional Sciences, 2022)
The paper is focusing on awareness and attitude of the employees towards HRM practices viz.,recruitment and selection, training and development and performance evaluation adopted by the commercialbanks. The paper is based on primary sources collected from 300 employees serving in commercial banks inShivamogga District. The study is confined to bank branches selected by using the purposive samplingmethod. There is no significant difference between recruitment and selection policies and practices, trainingand development practices, performance evaluation in commercial banks.